Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/13607863.2021.2019192
|View full text |Cite
|
Sign up to set email alerts
|

Does physical exercise improve the capacity for independent living in people with dementia or mild cognitive impairment: an overview of systematic reviews and meta-analyses

Abstract: Objective To summarise existing systematic reviews which assessed the effects of physical exercise on activities of daily living, walking, balance and visual processing in people with dementia or mild cognitive impairment Methods In this overview of systematic reviews and meta-analyses, seven electronic databases were searched to identify eligible reviews published between January 2015 and April 2021. Results A total of 30 systematic reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Numerous studies have shown that physical exercise is associated with positive effects on brain health ( 23 25 ). High levels of aerobic exercise have been associated with improved brain volume and factors of cognitive decline ( 26 , 27 ). Some studies have shown that aerobic exercise can boost brain plasticity ( 28 ), reduce hippocampal atrophy ( 29 ), and even increase the hippocampus ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that physical exercise is associated with positive effects on brain health ( 23 25 ). High levels of aerobic exercise have been associated with improved brain volume and factors of cognitive decline ( 26 , 27 ). Some studies have shown that aerobic exercise can boost brain plasticity ( 28 ), reduce hippocampal atrophy ( 29 ), and even increase the hippocampus ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that a higher dose of PA (i.e., higher intensity or frequency) confers more cognitive health benefits (Gallardo-Gómez et al, 2022; Sanders et al, 2019). Another reason is that participation in multiple types of PA activities (e.g., aerobic exercise, resistance training, flexibility, coordination, and balance) is more effective in improving global cognition and the activities of daily living skills compared to a single form of PA (Begde et al, 2021; Huang et al, 2022; Rezola-Pardo et al, 2020). For example, a recent clinical trial conducted in Spain showed that a PA intervention with multiple types of PA conferred greater improvements in physical performance than a walking intervention and can therefore support a more independent life for older adults (Rezola-Pardo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In its implementation, GR follows a multidimensional approach including diagnostic and therapeutic measures. Physical exercise is a cornerstone of GR and focuses on improving mobility, endurance, balance, and strength, which are relevant predictors for independent living [ 8 11 ]. Even though several months of exercise are necessary to most effectively improve balance and strength [ 12 , 13 ], the average length of stay in inpatient GR is limited to three weeks throughout Europe [ 6 ].…”
Section: Introductionmentioning
confidence: 99%